Crime, justice and human rights - Weber, Leanne; Marmo, Marinella; Fishwick, Elaine (Basingstoke, Hampshire Palgrave Macmillan, 2014)
"Crime, Justice and Human Rights is an introduction to the philosophy, law and politics of human rights, uniquely tailored to criminologists and criminal justice practitioners. Integrating human rights and criminological frameworks across a range of subject areas - from criminalization and state crime, to crime prevention and critical analyses of the operation of the police, courts and penal system - the authors highlight both the potential and the limitations of human rights in informing new directions in criminology. Featuring case material from Europe, North America, Australia and beyond, this critical, multidisciplinary text supports the teaching of human rights across a wide range of criminological topics, and assists students, researchers and independent readers to incorporate human rights paradigms into their criminological analysis"-- Provided by publisher.
Machine generated contents note: -- PART I: UNDERSTANDING HUMAN RIGHTS 1. The Origins and Idea of Human Rights 2. International Human Rights Law 3. Human Rights and Civil Society 4. Collective Rights and Discrimination5. Integrating Criminology and Human Rights PART II: APPLYING HUMAN RIGHTS IN CRIMINOLOGY6. Criminal Law 7. Crime Prevention8. Policing 9. Criminal Courts 10. Detention11. Juvenile Justice12. Victims PART III: A CRIMINOLOGY FOR HUMAN RIGHTS13. Future Directions.
Keywords: Human rights; Criminology; Criminal justice, Administration of